Multinucleate cell angiohistiocytoma: a case series and literature review - Carolyn Szwed; Malgorzata Maj; Lidia Rudnicka; Joanna Czuwara (Polish Journal of Pathology)
Multinucleate cell angiohistiocytoma (MCAH) is a rare benign cutaneous entity. It classically presents as slowly progressive erythematous to violaceous papules on the distal extremities of middle-aged or elderly women. The entity may clinically resemble granuloma annulare, lichen planus, and several cutaneous vascular proliferations. Histologically, MCAH is characterized by vascular proliferation within the upper and mid-dermis, a mild perivascular inflammatory infiltrate, and characteristic bizarre-shaped multinucleate cells. To date, less than 200 cases have been reported in the literature. We present five of the best examples diagnosed in our department to further elucidate this peculiar entity for pathological recognition.